The Protective Effect of a Novel Cross-Linked Hemoglobin-Based Oxygen Carrier on Hypoxia Injury of Acute Mountain Sickness in Rabbits and Goats - Zhang, Jie; Wu, Yue; Peng, Xiao-Yong; Li, Qing-Hui; Xiang, Xin-Ming; Zhu, Yu; Yan, Qing-Guang; Lau, Billy; Tzang, Feichuen; Liu, Liang-Ming; Li, Tao (Frontiers in Physiology, 2021)
Hypoxia is the major cause of acute altitude hypoxia injury in acute mountain sickness (AMS). YQ23 is a kind of novel bovine-derived, cross-linked hemoglobin-based oxygen carrier (HBOC). It has an excellent capacity for carrying and releasing oxygen. Whether YQ23 has a protective effect on the acute altitude hypoxia injury in AMS is unclear. To achieve this goal, the hypobaric chamber rabbit model and plain-to-plateau goat model were used, and the effects of YQ23 on the ability of general behavior, general vital signs, Electrocardiograph (ECG), hemodynamics, vital organ injury markers, and blood gases in hypobaric chamber rabbits and plain-to-plateau goats were measured. Our results showed that the ability of general behavior (General Behavioral Scores, GBS) (GBS:18±0 vs 14±0.5, p<0.01) and the general vital signs weakened (Heart rate (HR, beats/minute):253.5±8.7 vs 301.1±19.8, p<0.01; Respiratory rate (RR, breaths/minute): 86.1±5.2 vs 101.2±7.2, p<0.01) after exposure to plateau environment. YQ23 treatment significantly improved the ability of general behavior (GBS:15.8±0.5 vs 14±0.5, p<0.01) and general vital signs (HR (beats/minute):237.8±24.6 vs 301.1±19.8, p<0.01; RR (breaths/minute): 86.9±6.6 vs 101.2±7.2, p<0.01). The level of blood PaO2(mmHg) (115.3±4.7 vs 64.2±5.6, p<0.01) and SaO2(%) (97.7±0.7 vs 65.8±3.1, p<0.01) sharply decreased after exposure to plateau, YQ23 treatment significantly improved the blood PaO2 (mmHg) (97.6±3.7 vs 64.2±5.6, p<0.01 )and SaO2 (%) (82.7±5.2 vs 65.8±3.1, p<0.01).The cardiac ischemia and injury marker was increased(troponin (TnT, μg/L): 0.08±0.01 vs 0.12±0.02, p<0.01), as well as the renal(blood urea nitrogen (BUN, mmol/L): 6±0.7 vs 7.3±0.5, p<0.01) and liver injury marker (alanine aminotransferase (ALT, U/L): 45.8±3.6 vs 54.6±4.2, p<0.01) was increased after exposure to a plateau environment. YQ23 treatment markedly alleviated cardiac ischemia（TnT(μg/L): 0.10±0.01 vs 0.12±0.02, p<0.01) and mitigated the vital organ injury. Besides, YQ23 exhibited no adverse effects on hemodynamics, myocardial ischemia, and renal injury. In conclusion, YQ23 effectively alleviates acute altitude hypoxia injury of AMS without aside effects. Key Words: YQ23, hemoglobin-based oxygen carrier (HBOC), acute mountain sickness (AMS), carrying and releasing oxygen